2005
DOI: 10.1111/j.1365-2133.2004.06338.x
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid antigen 1 isoforms: potential new target autoantigens in multiple sclerosis?

Abstract: These results raise the possibility that a subset of patients with MS develops an autoantibody response to the neuronal variants of BPAG1. These findings potentially open the avenue of neuronal BPAG1 variants being novel targets of autoantibodies in neurological diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 23 publications
(30 reference statements)
2
46
0
1
Order By: Relevance
“…Conceivably, an autoimmune response initially directed against a neuronal isoform of BPAG1 (BPAG1-n) encoded by the dystonin gene may secondarily trigger an autoimmune response against the epithelial isoform of BPAG1, according to the ''epitope spreading'' phenomenon (Fairley et al, 2004). The two isoforms share the same sequence in their terminal portion, which is recognized by anti-BPAG1 antibodies from BP patients (Laffitte et al, 2005). Recombinant BPAG1 fragments have been identified in cerebrospinal fluid from patients with multiple sclerosis (Laffitte et al, 2005), and serum from BP patients with neurological diseases recognized BPAG1 in mouse skin and brain extracts (Li et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, an autoimmune response initially directed against a neuronal isoform of BPAG1 (BPAG1-n) encoded by the dystonin gene may secondarily trigger an autoimmune response against the epithelial isoform of BPAG1, according to the ''epitope spreading'' phenomenon (Fairley et al, 2004). The two isoforms share the same sequence in their terminal portion, which is recognized by anti-BPAG1 antibodies from BP patients (Laffitte et al, 2005). Recombinant BPAG1 fragments have been identified in cerebrospinal fluid from patients with multiple sclerosis (Laffitte et al, 2005), and serum from BP patients with neurological diseases recognized BPAG1 in mouse skin and brain extracts (Li et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that accumulation of neurofilaments might induce a tolerance breakdown against the neuro-isoform of BPAG1, that could subsequently led to a cross reaction against the epidermal form of BPAG1 [9, 11, 13, 17]. However, this hypothesis has never been clearly demonstrated and the expression of the homologous part of the epidermal and neuronal isoform of BPAG1 in the human brain remains debated [17, 18]. Therefore, we were prompted to assess the prevalence of neurological disorders in a series of BP patients.…”
Section: Discussionmentioning
confidence: 99%
“…El mecanismo patogénico de esta asociación se desconoce actualmente, aunque un trabajo apunta a que puede existir una reactividad cruzada entre las isoformas epitelial y neural de BPAG1 tras el acontecimiento neurológico. Esto daría lugar a la exposición al sistema inmunológico de la forma neural, lo que desencadenaría la respuesta con autoanticuerpos contra la isoforma epitelial y, consecuentemente, la enfermedad ampollosa 10 . Este fenómeno se ha postulado al demostrarse experimentalmente que el suero de pacientes con PA y enfermedad neurológica reaccionaba contra extractos de piel y cerebro de ratones 11 .…”
Section: Introductionunclassified